2013
DOI: 10.1177/1363461512475025
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability and mental health in Afghanistan: Looking beyond war exposure

Abstract: This study examined the prevalence of mental distress among groups in Afghanistan considered to be at risk. Data were drawn from a representative cross-sectional disability survey carried out in Afghanistan including 5,130 households in 171 clusters throughout the 34 provinces of the country. The sample included 838 nondisabled control participants aged above 14, and 675 disabled participants. Results showed that various vulnerable groups (disabled people, the unemployed, the elderly, minority ethnic groups, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 60 publications
2
31
0
1
Order By: Relevance
“…We heard from numerous colleagues that the paper expressed long held concerns they had had about: (1) the lack of explanatory power of the trauma focused or ' direct exposure' model and its overly narrow focus on treating war related PTSD; (2) the unrecognised and powerful in£uence of daily stressors on the mental health of war a¡ected populations; and (3) the need for multi-level or ecological interventions that address daily stressors, as well as enduring posttraumatic stress reactions. Trani and Bakhshi's (2013) research found that mental health in Afghanistan was linked to increased social exclusion present before war, driving home the importance of examining the maintenance and exacerbation of pre war stressors in conceptualising daily stressors. We reiterate that we were hardly the ¢rst nor only researchers to consider the importance of environmental stressors a¡ecting civilians in con£ict zones.…”
Section: Reactions To the 2010 Papermentioning
confidence: 99%
“…We heard from numerous colleagues that the paper expressed long held concerns they had had about: (1) the lack of explanatory power of the trauma focused or ' direct exposure' model and its overly narrow focus on treating war related PTSD; (2) the unrecognised and powerful in£uence of daily stressors on the mental health of war a¡ected populations; and (3) the need for multi-level or ecological interventions that address daily stressors, as well as enduring posttraumatic stress reactions. Trani and Bakhshi's (2013) research found that mental health in Afghanistan was linked to increased social exclusion present before war, driving home the importance of examining the maintenance and exacerbation of pre war stressors in conceptualising daily stressors. We reiterate that we were hardly the ¢rst nor only researchers to consider the importance of environmental stressors a¡ecting civilians in con£ict zones.…”
Section: Reactions To the 2010 Papermentioning
confidence: 99%
“…As promoted by the World Health Organization and the World Organization of Family Doctors, integration of mental health care into primary health care services may be the most effective way to provide access to mental health care that is otherwise unavailable in most parts of the world (WHO & Wonca, 2008). This approach may be viable in Iraq; a systematic program to integrate mental health into 1200 primary care centers across Iraq was begun in 2008 (Sadik, Abdulrahman, Bradley, & Jenkins, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…O cenário onde se desenvolveram os estudos, em geral, corresponde aos três níveis de atenção à saúde. Notaram-se diferentes espaços onde o conceito foi discutido, desde o ambiente domiciliar (Trani & Bakhshi, 2013;Tah et al, 2015;Zanatta et al, 2018a;Amancio et al, 2019), até cenários como o local de trabalho (Fatini et al, 2014;Takahashi et al, 2014;Smith et al, 2015;Santos et al, 2015) , a escola (Anjos et al, 2012;Atanázio et al, 2013;Jesus & Monteiro, 2016;Marushima et al, 2018) e a universidade (Meneghel et al, 2003;Mussi et al, 2012;Olveira et al, 2013;Carrillo et al, 2014;Zanatta & Motta, 2015;D'Arco et al, 2016;Sequeira et al, 2017;Soares et al, 2018), traduzindo um pouco a aproximação à promoção da intersetorialidade a que o conceito se propôs nos seus quadros conceituais originários.…”
Section: Discussionunclassified